Implementation of education for sustainable development in geography subjects among trainee teachers - Sumayyah Aimi Mohd Najib; Benedic Sat Anak Pasang (International Journal of Evaluation and Research in Education (IJERE), 2022)
Education for sustainable development (ESD) is a truly positive measure. This study was unique in that it made students aware of the positive qualities. Therefore, ESD is crucial to be inculcated among students. If the students are provided with in-depth knowledge related to sustainable development, hence it is not impossible for the sustainable development concept to come true. The study was conducted at Universiti Pendidikan Sultan Idris (UPSI), Perak, Malaysia. The respondents involved are geography students who have undergone teacher training in semester 7 and semester 8. This study also focused on the level of knowledge and the level of mastery among trainee teachers on ESD. In addition, this study was carried out for the trainee teachers to obtain the data the on the implementation of ESD values in teaching and learning (T&L) of geography subjects via a survey. Result showed that T&L of geography subjects shall be interesting and challenging so that students can enjoy fun learning. Teachers need to be smart in finding approaches to be tailored to the curriculum, especially in the geography subjects.